Pengaruh Metode Bercerita Terhadap Perkembangan Bahasa Anak Di RA IP Qurrota A'yun Ngrandu Nglorog Sragen Tahun Ajaran 2015/2016 - Laila Nuril Husna, Irna; , Dra. Surtikanti, M.Pd (2016)
The purpose of this research is to know the influence of storytelling on the development of children's languageGroup A at RA IP Qurrota A'yun Ngrandu Nglorog Sragen academic year 2015/2016. This research is a research experiment with design research One-Group Pretest-Postest design. The subject of this research is the learners Group A at RA IP Qurrota A'yun Ngrandu Nglorog Sragen academic year 2015/2016. Data on children's development language gathered through observation and documentation. Data analysis technique used is the t-test. The results of the data analysis the value tcount-15.135 ≤ - ttable1,753then Ho denied and Ha is received. Thus it can be concluded that the storytelling effect the development language of children'sGroup ARA IP Qurrota A'yun Ngrandu Nglorog Sragen academic year 2015/2016.